Edukasi dan Deteksi Dini Skizofrenia Berbasis Keluarga di Wilayah Kerja Puskesmas Talang Jaya Betung Tahun 2025 - Wikesy Wikesy; Elvi Sunarsih; Sri Utari (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Schizophrenia is a chronic mental disorder that significantly impacts social functioning, quality of life, and burdens families and communities. According to data from the Talang Jaya Betung Community Health Center, the number of schizophrenia cases increased from 45 in 2021 to 60 in 2024. This situation highlights the need for promotive and preventive efforts focused on improving public understanding of risk factors and the importance of early detection of schizophrenia. This community service activity aims to increase public and family knowledge about schizophrenia, its risk factors, and prevention efforts through a family-based educational approach. The implementation methods included mental health education, interactive discussions, distribution of educational media, and initial screening for schizophrenia risk factors in the community within the Talang Jaya Betung Community Health Center's work area. The target group was families with members at risk of mental disorders and the general public. Results showed increased public knowledge regarding the signs and symptoms of schizophrenia, risk factors such as family income, parenting styles, and family history, and increased awareness of the importance of the family's role in the prevention and early detection of schizophrenia. Furthermore, this activity also strengthens the role of health cadres in promoting mental health in the community. This community service activity is expected to contribute to reducing the risk of schizophrenia by strengthening the role of families and communities, as well as supporting community health center programs in promotive and preventive mental health efforts.